In Vitro Microvibration Increases Implantation Rate after Embryonic Cell Transplantation. Issue 5 (May 2017) - Isachenko, Vladimir; Sterzik, Karl; Maettner, Robert; Isachenko, Evgenia; Todorov, Plamen; Rahimi, Gohar; Mallmann, Peter; Strehler, Erwin; Pereligin, Igor; Alabarte, José Luis; Merzenich, Markus
In natural conditions the oocyte and embryo are subjected to ever-changing dynamic processes. However, the routine assisted reproductive technologies today involve the use of static in vitro culture systems. The objective was to determine whether there is any difference in the viability of embryos after in vitro culture under static and mechanical microvibration conditions. The viability of embryonic cells (9, 624 embryos) generated from 4, 436 couples after in vitro culture was evaluated. For groups ≤29, 30-34, 35-39, and ≥40 years, the following rates of high-quality embryos without fragmentation (two to four blastomeres on day 2; six to eight blastomeres and compacting morula on day 3; blastocyst, expanded and hatching blastocyst on day 5) were detected (static vs. vibration, respectively): 65% versus 71%, 44% versus 69%, 67% versus 76% (for statistically significant differences between respective rates in these three groups, p <0.05), and 67% versus 66% (p > 0.1). The following baby-take-home rates were determined for groups ≤29, 30-34, 35-39, and ≥40 years (static vs. vibration, respectively): 30% versus 31% (p > 0.1, increasing only on the level of tendency), 28% versus 37%, 23% versus 29%, and 9% versus 15% (differences between respective rates in these three groups with p < 0.05). It was concluded that in vitro culture of embryos under microvibration (with a mimic of conditions in nature whereby oviductal fluid is mechanically agitated by the epithelial cilia) significantly increases the baby-take-home rate for patients 30 years and older.